Energy exchange in age physiology: regulation of metabolism and adaptive reactions - Robiyaxon Akmal qizi Qambaraliyeva; Zarnigorbegim Ibrohimbek qizi Xabibullayeva; Ra’no Amanullayevna Aliyeva (Science and Education, 2025)
In this article we consider the characteristics of energy exchange at different stages of human life with emphasis on physiological changes occurring with age. Special attention is paid to hormone regulation, mitochondrial role, mechanisms of stress adaptation, as well as prevention of age-related metabolic disorders. Present modern scientific views on the relationship of metabolism and aging processes, substantiated directions of maintenance of metabolic health in old age. The analysis takes into account biological, clinical and behavioral factors.